Penerapan Aplikasi telunjuk Sakti dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wonogiri - Kusdianingsih, Runi; Winduro, Wirid (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
In order to organize quality public services based on innovative smartphones, the Population and Civil Registration Office of Wonogiri Regency made an innovation in the form of the Telunjuk Sakti application for applications for population administration document services. This study aims to describe the application of the Telunjuk Sakti application in population administration services at the Population and Civil Registration Office of Wonogiri Regency using the Technology Acceptance Model (TAM) theory. This research uses descriptive qualitative research methods. The data collection techniques used were observation, interview and documentation. The results of this study indicate that the acceptance of the Telunjuk Sakti application among managers and users has fulfilled two perceptions of the Technology Acceptance Model (TAM), namely perceived usefulness and perceived convenience. Based on the perception of usefulness, it makes work faster, improves performance and increases work productivity. While based on the perception of user convenience, it can bee seen that the Telunjuk Sakti application is easy for users to use, including easy to learn and become proficient, controllable, clear and understandable.